Musicological and Ethnomusicological Perspectives - Villén, AV (Bloomsbury, 2023)
Popular music and religion are in a doubly challenged position as an amalgamated subject area of academic enquiry. On the one hand, the reactionary conventions of music education prevail, whereby music tends to be conceived as High Art and thus dominated by the classical canon, in both practical tuition and scholarly analysis. Consequently, the more music is associated with so-called ‘extramusical’ or ‘functional’ dimensions – such as entertainment or religion – the fewer resources are devoted to it in higher education. On the other hand, there is an exclusionary tension between the popular and the religious, or between entertainment and religion, on the basis of different philosophies and conceptions of the world especially, regardless of the vast quantities of religious devotees. Thus, until the twenty-first century it was equally rare to encounter discussion about religiosity in popular music studies as it was to run into deliberation about music in the study of religions.
Keywords: uskonto ja uskonnot; musiikki; uskonnollisuus; musiikkifilosofia; populaarimusiikki; etnomusikologia; populaarikulttuuri